Pakistan Development Update, April 2021 : Navigating in Uncertain Times - World Bank (World Bank, Washington, DC, 2021)
The World Bank Pakistan Development Update (PDU) provides an update on the Pakistani economy, its economic outlook, together with the development challenges it faces and the structural reforms that should be considered. The report begins with a chapter on recent economic developments, with sections on the real sector and economic growth, monetary and financial sector developments, the external sector, and fiscal policy and public debt. The second chapter provides the medium-term macroeconomic outlook, describes risks and challenges, and structural reform needs. This is followed by the focus topic section on the impact of the Coronavirus (COVID-19) crisis on the private sector.